Knowledge Economy Gaps, Policy Syndromes and Catch-up Strategies: Fresh South Korean Lessons to Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
Africa's overall knowledge index fell between 2000 and 2009. South Korea's economic miracle is largely due to a knowledge-based development strategy that holds valuable lessons for African countries in their current pursuit towards knowledge economies. Using updated data (1996-2010), this paper presents fresh South Korean lessons to Africa by assessing the knowledge economy (KE) gaps, deriving policy syndromes and providing catch-up strategies. The 53 African frontier countries are decomposed into fundamental characteristics of wealth, legal origins, regional proximity, oil-exporting, political stability and landlockedness. The World Bank's four KE components are used: education, innovation, information & communication technology (ICT) and economic incentives & institutional regime. Absolute beta and sigma convergence techniques are employed as empirical strategies. With the exception of ICT for which catch-up is not very apparent, in increasing order it is visible in: innovation, economic incentives, education and institutional regime. The speed of catch-up varies between 8.66% and 30.00% per annum with respective time to full or 100% catch-up of 34.64 years and 10 years. Based on the trends and dynamics in the KE gaps, policy syndromes and compelling catch-up strategies are discussed. Issues standing on the way to KE in Africa are dissected with great acuteness before South Korean relevant solutions are provided. The paper is original in its provision of practical policy initiatives drawn from the Korean experience to African countries embarking on a transition to KE.
Keywords: O10; O30; O38; O55; O57; 330; Knowledge economy; Catch-up; South Korea; Africa